Optical excitation of electromagnons in hexaferrite - Hiroki Ueda; Hoyoung Jang; Sae Hwan Chun; Hyeong-Do Kim; Minseok Kim; Sang-Youn Park; Simone Finizio; Nazaret Ortiz Hernandez; Vladimir Ovuka; Matteo Savoini; Tsuyoshi Kimura; Yoshikazu Tanaka; et al. (Physical Review Research, 2022)
Understanding ultrafast magnetization dynamics on the microscopic level is of strong current interest due to the potential for applications in information storage. In recent years, spin-lattice coupling has been recognized as essential for ultrafast magnetization dynamics. Magnetoelectric multiferroics of type II possess intrinsic correlations among magnetic sublattices and electric polarization (P) through spin-lattice coupling, enabling fundamentally coupled dynamics between spins and lattice. Here, we report on ultrafast magnetization dynamics in a room-temperature multiferroic hexaferrite possessing ferrimagnetic (FM) and antiferromagnetic sublattices, revealed by time-resolved resonant x-ray diffraction. A femtosecond above-bandgap excitation triggers a coherent magnon in which the two magnetic sublattices entangle and give rise to a transient modulation of P. A microscopic mechanism for triggering the coherent magnon in this FM insulator based on the spin-lattice coupling is proposed. Our finding opens a general pathway for ultrafast control of magnetism.